Pencatatan Laporan Keuangan Sederhana pada UMKM Hans Snack & Cake Desa Citeko Kabupaten Bogor - Gita Atiatul Uzma E; Nispi Yani Sya’banniyah; Erni Yuningsih; Rachmat Gunawan; Irham Maolana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Hans Snack and Cake is an MSME that produces various kinds of snacks consisting of tart cakes, pastries and bread. The potential of MSMEs is in demand by many consumers so they have high sales, but there is still a low understanding of financial management which causes MSMEs not to know their financial position. This service provides training on the importance of financial recording with the aim of enabling MSMEs to see financial performance and be able to divide budgets effectively so that they are more structured and mature. Training provided regarding Cost of Goods Production Reports (HPP) and Profit and Loss Reports. The methods used were interviews, observation and training programs. The success of this service provides benefits for students, MSMEs and is able to encourage MSMEs to improve financial management. Community involvement in this service is the key to the success of this program.